Equilibrium Studies of Lanthanide(III) Complexes of (1-Phenyl-3-methyl-4-benzoyl-pyrazol-5-one) Anthranilic Acid and (1-Phenyl-3-methyl-4-benzoyl-pyrazol-5-one) Aminoantipyrine - Mahalakshmi Sita, N. (Asian Journal of Chemistry, 2010)
The stability constants of lanthanide(III) complexes of (1-phenyl- 3-methyl-4-benzoyl-pyrazol-5-one) anthranilic acid [Ln(PMBAA)2NO3] and (1-phenyl-3-methyl-4-benzoyl-pyrazol-5-one) aminoantipyrine [Ln(PMBAAP)3] complexes have been determined by potentiometric method and the values obtained practically agree for the whole series of lanthanide for both types of complexes. The IR spectral studies show that in both complexes the ligands are similarly coordinated by carbonyl oxygen atoms. In the [Ln(PMBAA)2NO3] complexes the nitrate ion also takes part in coordination. The multiplet pattern of NMR spectra which partially disappears show a more rigid pattern for PMBAA than for PMBAAP.